Illustrator CS5 bible - Alspach, Ted (Indianapolis, IN Wiley Pub, 2010)
Introduces Adobe's Illustrator graphics program, providing the basics plus drawing and painting tips, and offers information on working with files and customization
Illustrator basics: What's new in Illustrator CS5? ; Understanding Illustrator's desktop ; Working with Illustrator documents ; Understanding drawing and painting techniques ; Creating objects, graphs, and symbols ; Learning how to select and edit ; Understanding color, gradients, and mesh -- Putting Illustrator to work: Using Illustrator to organize objects ; Working with type ; Using creative strokes and fills with patterns ; Applying transformations and distortions ; Using path blends, compound paths, and masks ; Using live trace ; Using live paint -- Mastering Illustrator: Working with graphic styles and effects ; Creating 3-D in Illustrator ; Customizing and automating Illustrator -- Getting art out of Illustrator: Understanding PostScript and printing ; Creating web graphics ; Illustrator workflow -- Appendix: Shortcuts in Illustrator CS5
"16-page full color insert, showcases cutting-edge work by leading Illustrator artists"--Cover
"Published simultaneously in Canada"--T.p. verso
Includes index
1
Keywords: Adobe Illustrator (Computer file); Adobe Illustrator (Computer software); Computer graphics; Computer graphics